Calculation Of Evaporation Loss in Tank Y and Tank Z at SA Field PT X Prabumulih - Andalucia, Sefilra (Journal of Earth Energy Engineering, 2023)
One of the facilities that plays an important role in the petroleum industry both in the fields of upstream oil and gas, downstream oil and gas, shipping and commerce is fluid storage area which is better known as a storage tank. Storage tank is very influential on the petroleum production process. Storage has an important role to accommodate and store fluid in the process of fluid distribution or fluid delivery from the production collector to the next destination such as production collection centers, refineries, and shipping. The storage tank used in SA Field is a fixed tap type tank (fixed roof tank). Fixed roof tanks are the most common type of tank among all tank cylinder and have a fixed conical roof with / without roof structure. Oil in storage tanks can experience losses. Losses are the disappearance or shrinkage of petroleum. Losses in this tank are caused by evaporation loss which is influenced by the temperature of the petroleum as well as the temperature from the weather outside the tank and the amount of free space in the tank. If the larger the free space in the tank, the greater the potential for evaporation of crude oil in the tank. In this study, an analysis of the factors causing evaporation loss will be carried out, calculation of evaporation loss, and calculation of the number of financial losses caused by evaporation loss in Tank X and Tank Y. Briefly, this research will be useful as one of the important references for the industry to find out the number of financial losses caused by evaporation loss.